Less Stringent Global Health Treaties: Insights from Various Regimes - Albar, Rafsi Azzam Hibatullah (Faculty of Law Universitas Lampung, 2024)
Global health captured significant attention in the international legal community after COVID-19 struck the world. The formulation of a pandemic treaty sparked discourse on how the regime's treaties should be designed: whether they should adhere strictly to stringent measures or adopt more lenient approaches. This paper argued in favor of the latter. Initially, the research explained the objectives and characteristics of global health treaties as a primary component of global health governance. Then, it compared two sides of the debate on flexibility: the idealism of full commitment by all and the pragmatism of willingness to participate and enforce. With the facts obtained, a contextual analysis of the diplomatic dynamics at the World Health Organization (WHO) was performed to understand the constraints of treaty-making at the main international platform for public health. Lastly, the research proposed four main ideas that make up the ideal party: cognizance of pre-existing realities, allowance for differentiated commitment levels, careful linguistic choices, and the inclusion of a minimal yet effective enforcement mechanism.